Estudos das proteínas ligantes à DCRA e DSCR1 (envolvidas com a síndrome de Down) utilizando a metodologia do duplo-híbrido - Silveira, Henrique César Santejo (2003)
The genes DCRA and DSCR1 are located in the Down Syndrome Critical Region , a specific portion of human chromosome 21 responsible for the main traits of the disease. In the present work we have used the two-hybrid system as an approach to find proteins that interact with DCRA and DSCR1. This method is based on the properties of the yeast GAL4 protein, which consists of separable domains responsible for DNA-binding and transcriptional activation. The open reading frames of DCRA and DSCR1 were cloned in frame with the GAL4 DNA-binding domain. These constructions were used to analyse protein interactions using a human foetal brain cDNA library, cloned in frame with the GAL4 transcriptional activation domain. No DCRA protein partners were found in any of the screenings performed; nevertheless, the analysis allowed the detection of several false positive clones. In the analysis of DSCR1 we identified two proteins, UXT (ubiquitously expressed transcript) and APLP1 (amyloid precursor-like protein 1). These results may help elucidate a new function for DSCR1 in the nucleus, probably related gene expresion.